XX դարի 20-30-ական թվականների քրդական ապստամբությունները և թուրք–իրանական հարաբերությունները - Բայբուրդյան, Վահան («Զանգակ - 97»)
The Convention of Sevr was revised in 1923 during Lozan Confrence by the common wish of Great Powers. As a result the problems of Armenia and Kurdistan specified in the articles of the Convention were removed from the agenda of international discussions.
Keywords: Պատմություն